Respuesta :
Answer:
To create function h, function f was translated 2 units to the right, translated 4 units down and reflected across the y-axis.
Step-by-step explanation:
Since f(x) = x^3 is transformed to h(x) = -(x+2)^3-4, by
1. Adding 2 to x in x³ to give f'(x) = f(x + 2) = (x + 2)³.
2. We now translate f(x + 2) down by subtracting 4 from f(x + 2) to give
f''(x) = f'(x) - 4 = f(x +2) - 4 = (x + 2)³ - 4.
3. We now reflect f'(x) across the y-axis by multiplying (x + 2)³ by -1 to get
h(x) = -(x + 2)³ - 4.
Answer:
its 2 to the left, 4 units down, and over the x axis.
Step-by-step explanation:
not my answer just the one from the comments